Absolute quantitation of protein therapeutics in biological matrices by enzymatic digestion and LC–MS. (November 2011) - Li, Fumin; Fast, Douglas; Michael, Steve
The advancement of biotechnology has led to an increase in biotherapeutic drugs, especially recombinant proteins and monoclonal antibodies. Ligand-binding assays or immunoassays are the standard methods of choice in pharmacokinetic studies in support of drug discovery and development for protein therapeutics. LC–MS-based methodologies are increasingly used as alternatives to immunoassays for absolute protein quantitation in biological samples. We review recent advancements in absolute quantitation of protein therapeutics in biological matrices by enzymatic digestion and LC–MS.